PENGARUH PENGEMBANGAN APARATUR TERHADAP KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN (Studi pada Kantor Samsat Dinas Pendapatan Daerah Prov. Kaltim) - Syachrumsyah Asri (Jurnal Borneo Administrator, 2008)
The number of the public service customer growth as fast as their satisfaction. Public service and their customer satisfaction are being critical point because this phenomena. How the government apparatus providing their service in order to make their costumers satisfy? In this research result shows that the strategy of human resource development through education, training, and development affect human resource quality and this give further effect on the government performance that can be seen from the public service quality. At last, the service quality will determine the improving public or customer satisfaction. The information about what costumer need and what customer want must be consider for providing good public service.  Key Words: HRD, Service Quality, Customer Satisfaction, Public Service.